Thermostability improvement of xylanase using error-prone polymerase chain reaction [electronic resource] - 556236 Mohd. Khairul Hakimi Abdul Wahab (2013)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2013